DIGITAL MARKETING SEBAGAI STRATEGI KOMUNIKASI PEMASARAN â€œWARUNG RS (RAMASHITA)â€ DALAM MENINGKATKAN JUMLAH KONSUMEN - Ni Luh Indiani; Ni Putu Andini Desiyanti Laksmi (Forum Manajemen, 2021)
Technological developments have markedly changed the way a business works, especially a culinary business that named Warung RS (ramashita) located in Dalung area, North Kuta District, Badung Regency, Bali. This business is still relatively new, but consumers remain loyal to the message in the pandemic and sales of vegetarian culinary products are increasingly Increased. This phenomenon is a result of business entering the digital age in social media. Marketing not intensively conducted by the owner of this business, but it is consumers who are encouraged to market it virally in social media especially social media Instagram and Facebook. In this article the author descriptively analyze the behavior of consumers in digital marketing that has been sales of these culinary products. The analysis was conducted with a case study and attributed in the literature on consumer behavior and digital marketing. This article aims to explaining consumer behavior in the digital age so that it can be input in determining the marketing strategies of culinary businesses in the future as well as becoming consumer research thinking materials in the future.